2018
DOI: 10.3390/land7020045
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Smallholder Livelihoods in the Ecuadorian Highlands: A Comparison of Agroforestry and Conventional Agriculture Systems in the Indigenous Territory of Kayambi People

Abstract: Smallholder farming constitutes an important but marginalized sector, responsible for most of the world's agricultural production. This has a significant influence in the land use/cover change process and agrobiodiversity conservation, especially in mountainous regions of the developing world. Thus, the maintenance of sustainable smallholder farming systems represents a key condition for sustainable land management and to safeguard the livelihoods of millions of rural households. This study uses a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
3
25
0
3
Order By: Relevance
“…A maximum property of 2 ha is a common threshold for the distinction between small and larger farms [10,[14][15][16]. Seldom, 5 ha is the critical value [2,17]. A second definition of small farms refers to farm ownership.…”
Section: How Small Is Small?-definition Of a Small Farmmentioning
confidence: 99%
See 3 more Smart Citations
“…A maximum property of 2 ha is a common threshold for the distinction between small and larger farms [10,[14][15][16]. Seldom, 5 ha is the critical value [2,17]. A second definition of small farms refers to farm ownership.…”
Section: How Small Is Small?-definition Of a Small Farmmentioning
confidence: 99%
“…A second definition of small farms refers to farm ownership. Accordingly, small farms are family-operated (sometimes including more than one household) with limited or no hired labour [10,14,17,18]. In high-income countries, the generated value is also a common indicator: for example, the USDA defines small farms as farms with less than $100,000 in value of annual production and distinguishes them from "non-commercial" farms which make less than $50,000 per year [19].…”
Section: How Small Is Small?-definition Of a Small Farmmentioning
confidence: 99%
See 2 more Smart Citations
“…The removal or destruction of forest cover resulted in significant losses of tropical and global biodiversity, owing to the destruction of forest-based habitats and species [2]. Tree cover continuously decreased in the tropics for the past 17 years [3]. Deforestation is primarily a concern for developing countries in the tropics [4,5], where significant agricultural demand for land is often coupled with a lack of economic incentives for forest Study of the biological structure of agroforestry systems as indicated by the number and abundance of species provides insights into the relative importance of different plant species, and helps identify important elements of plant diversity, such as threatened and economically important species, to increase their abundance and productivity [38,39] Biodiversity measures (i.e., species diversity and species richness) are widely used as indicators of ecosystem health and human influence on ecological systems [38,40], and are factored in the monitoring of the status of agroforests and in successful conservation management [41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%